The relationships between emotional intelligence, sensation seeking, and marital satisfaction among female teachers - Siavoshi, Hatam; Jahanian, Ali; Abbasi Asl, Mojtaba; Mafakheri, Mohammad (Social Determinants of Health, 2016)
Background: Marriage and matrimony is an issue widely affected by emotional intelligence and sensation seeking. The purpose of the present study was to investigate the relationships between emotional intelligence, sensation seeking, and marital satisfaction among female teachers in the city of Borujerd. Methods: The statistical population consisted of all married female teachers in the city of Borujerd among whom 100 were selected as the sample using random cluster sampling method. To collect the data, Enrich marital satisfaction, Bar-On emotional intelligence, and Zuckerman sensation seeking questionnaires were used. Data analysis was performed using SPSS software running Pearson’s correlation test and stepwise regression. Results: The results of the analysis indicated that, with a significance level of P<0.001, there was a negative and significant relationship between sensation seeking and marital satisfaction, and there was a positive and significant relationship between emotional intelligence and marital satisfaction. Also, a statistically significant relationship was found between sensation seeking and emotional intelligence. Due to the inverse relationship, any increase in sensation seeking scores results in a decrease in marital satisfaction and vice versa. Moreover, because of the direct relationship between the two variables, any increase in emotional intelligence results in an increase in marital satisfaction. Conclusion: Considering the findings of the present study, sensation seeking and emotional intelligence have a significant relationship with marital satisfaction. The results of the study can help psychologists and counselors to pay more attention in marital satisfaction and affecting factors to enhance couples’ relationships.